Presenting a Model for Improving Customer Relationship Management with Sustainable Development Using a Meta-Synthesis Approach - Yazdani, Hossein; Gholipour Freydouni, Shahrbanoo; Rouholamini, Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The primary objective of this research is to develop a comprehensive model for improving Customer Relationship Management (CRM) with sustainable development using a meta-synthesis approach.Methodology: This study employs a qualitative meta-synthesis method, utilizing the seven-step model proposed by Sandelowski and Barroso (2007). A systematic literature review was conducted, analyzing both Persian and English academic articles published between 2010 and 2023. A total of 602 articles were initially reviewed, with 54 high-quality studies selected for further analysis. Key data were extracted, coded, and synthesized using Atlas.ti software, leading to the identification of critical dimensions and indicators.Findings: The research identified four key dimensions, eight components, and 53 indicators critical for improving CRM with sustainable development. The identified dimensions include: (1) Knowledge Development (empowerment and development, information technology and knowledge); (2) Organizational Behavior (organizational citizenship behavior, organizational factors); (3) Market Environment (political and economic conditions, market and customer factors); and (4) Managerial Factors (performance and financial factors, managerial and strategic factors). These findings align with several previous studies, confirming the importance of integrating sustainability into CRM practices.Conclusion: The study presents a comprehensive model that integrates CRM with sustainability, providing a roadmap for organizations to enhance customer relationships while promoting long-term sustainability. The findings underscore the importance of knowledge development, organizational behavior, market adaptability, and effective managerial strategies in fostering sustainable CRM practices. The model serves as a strategic guide for businesses aiming to balance customer satisfaction, profitability, and sustainability goals.